Use of a commercial ion chamber detector array for the measurement of high spatial‐resolution photon beam profiles. (4th October 2018) - Karimnia, Vida; Belley, Matthew D.; Rodgers, Robert; Price, Michael
Abstract: Linear accelerator (linac) commissioning and quality assurance measurements are time‐consuming tasks that often require a water tank scanning system to acquire profile scans for full characterization of dosimetric beam properties. To increase efficiency, a method is demonstrated to acquire variable resolution, photon beam profile data using a commercially available ion chamber array (0.5 cm detector spacing). Field sizes of 2 × 2, 5 × 5, 10 × 10, and 15 × 15 cm 2 were acquired at depths in solid water of d max, 5 cm, and 10 cm; additionally, beam profiles for field sizes of 25 × 25 and 40 × 40 cm 2 were acquired at 5 cm depth in solid water at x‐ray energies of 6 and 23 MV. 1D composite profiles were generated by combining discrete point measurements made at multiple couch positions. The 1D composite profile dataset was evaluated against a commissioning dataset acquired with a 3D water tank scan system utilizing (a) 0.125 cc ion chamber for 5 × 5, 10 × 10, 15 × 15, 25 × 25, and 40 × 40 field sizes and (b) a solid state detector for 2 × 2 cm 2 field size. The two datasets were compared to the gamma criteria at 1%/1 mm and 2%/2 mm tolerance. Almost all pass rates exceeded 95% at 2%/2 mm except for the 6 MV 2 × 2 cm 2 field size at d max . Pass rates at 1%/1 mm ranged from 51% to 99%, with an average pass rate of 82%. A fourfold reduction in MU was achieved for scans larger than 15 × 15 cm 2 using this method compared to the water tank scans. Further, dynamic wedge measurements acquired with the ion chamber array showed reasonable agreement with the treatment planning system. This method opens up new possibilities for rapid acquisition of variable resolution 2D–3D dosimetric data mitigating the need for acquiring all scan data with in‐water measurements.